Serum Vitamin D Levels in Premature Neonates with Retinopathy of Prematurity; Prevalence, Severity, and Types of Treatments; A Cross-Sectional Study from Iran, 2019-2020 - Ziba Mosayebi; Setareh Sagheb; Mohammad Reza Zarkesh; Marzieh Maddah; Mamak Shariat (Iranian Journal of Neonatology, 2025)
Background: Retinopathy of prematurity (ROP) is the leading cause of preventable blindness in premature infants. 1, 25-dihydro vitamin D (Vitamin D) is a critical metabolite for the homeostasis, growth, and development, with its receptors widely present in the structure of the eyes. This study aimed to investigate the potential relationships between serum vitamin D level and the prevalence, severity, and treatment types of ROP among neonates admitted to the neonatal intensive care unit (NICU).Methods: A cross-sectional study was conducted in Tehran, Iran, from 2019 to 2020. Seventy-five preterm neonates, either with a birth weight of ≤2000 grams or unstable conditions, were included in the study. Serum vitamin D levels were measured for all neonates immediately upon admission to the NICU. Additionally, a comprehensive eye examination was performed for ROP screening. Neonates who developed ROP were categorized into two groups: Type 1 (required treatment) and Type 2 (required no treatment or only close monitoring). The relationships between vitamin D levels and the severity and type of ROP treatment were then analyzed.Results: Among 75 newborns, ROP developed in zone 1 in 10 cases (13%), zone 2 in 50 cases (67%), and zone 3 in 15 cases (20%). Of all, 18 cases (24%) were classified as Type 1 and required treatment. The mean gestational age of neonates with Type 1 ROP was significantly lower than that of neonates in the other group (P= 0.028). Of all neonates, 38 (51%) had sufficient vitamin D levels, 15 (20%) had insufficient levels, and 22 (29%) were vitamin D deficient. When comparing vitamin D status between the groups, the results showed that the mean vitamin D level was lower in neonates with Type 1 ROP compared to those with Type 2 ROP. Additionally, the mean vitamin D level in neonates with zone 3 ROP was significantly higher (P=0.04) than in those with zones 1 and 2.Conclusion: The results of this study demonstrated a positive relationship between vitamin D levels and the zones affected by ROP. This finding suggests that prenatal vitamin D supplementation may have a beneficial effect in preventing abnormal angiogenesis and reducing the involvement of the posterior retinal pole.